Propuesta de mejoramiento de los procesos para la construcción de losas postensadas. - Díaz-Barboza, José Andrés (Instituto Tecnológico de Costa Rica, 2014)
The following report is the development of a proposal for improving the processes related with post-tensioning slabs, from VIVE Sabanilla Project, second phase, by company BILCO Costa Rica S.A. The specific objectives were: analyze the logical sequence of processes; identify sampling technique for productivity and performance; generate control measures performance and productivity; creating a control system for the process; develop a proposal for improvement in the areas of cost, productivity, quality and safety. In order to achieve them, the processes were studied in order to estimate the performance in terms of cost and Work time for each activity Productivity was measured using three techniques, Work Sampling, Five Minutes Rating and Crew Balance; these are used to determine the productivity of the process and the workers. The company can use the control system, the recommendations and the proposal in the areas of cost, productivity, quality and safety, in order to improve the construction of this system of slabs.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2014.
Keywords: Productividad; Rendimiento; Calidad; Seguridad Laboral; Análisis